ANALISIS PERBANDINGAN ALGORITMA ARITHMETIC CODING DAN LEMPEL ZIV WELCH (LZW) DALAM MENGKOMPRESI FILE AUDIO MP3 - Arief, Mhd. Abrar; Pristiwanto; Siregar, Saidi Ramadan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
MP3 audio files are a common format for storing and transmitting audio data, but file size can impact delivery time and memory capacity requirements. Compressing MP3 files is crucial for efficient transfer and storage space savings. Two popular lossless compression algorithms, namely arithmetic coding and Lempel-Ziv-Welch (LZW), play a significant role in determining how well MP3 audio files can be compressed without significant loss of quality. A comparative analysis between these two algorithms using criteria such as Compression Ratio, Ratio Compression, Redundancy, and Space Saving with the help of exponential methods indicates that arithmetic coding and LZW have total values of 10.1127 and 9.6047, respectively. This suggests that while arithmetic coding may be more efficient in terms of compression, LZW requires less effort. This comparison provides insights into the advantages and disadvantages of each algorithm, aiding in the selection of the most effective compression method for MP3 audio files.